Electrophysiological Correlates of the Autobiographical Implicit Association Test (aIAT): Response Conflict and Conflict Resolution - Marini, Maddalena; Agosta, Sara; Sartori, Giuseppe (Frontiers in Human Neuroscience, 2016)
The autobiographical IAT (aIAT) is an implicit behavioral instrument that can detect autobiographical memories encoded in an individual's mind by measuring how quickly this person can categorize and associate sentences related to a specific event with the logical dimensions true and false. Faster categorization when an event (e.g., I went to Paris) is associated with the dimension true than false indicates that that specific event is encoded as true in the individual's mind. The aim of this study is to investigate the electrophysiological correlates of the aIAT, used as a memory-detection technique (i.e., to identify which of two events is true). To this end, we recorded ERPs while participants performed an aIAT assessing which of two playing cards they had previously selected. We found an increased N200 and a decreased LPC (or P300) at the fronto-central sites when participants associated the selected playing card with the dimension false than true. Notably, both components have been previously and consistently reported in studies investigating deception. These results suggest that associating a true autobiographical event with the concept of false may involve the same cognitive processes associated with deception.